Integrasi Model Pembelajaran CIRC Berbantuan Google Sites untuk Meningkatkan Literasi Baca-Tulis Siswa SMP - Murti Murti; Jufri Jufri; Juanda Juanda; Romansyah Sahabuddin (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2025)
This study aims to develop and test the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by Google Sites in improving the literacy skills of junior high school students in Majene Regency. This study is a research and development (R&D) using the ADDIE model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques were carried out through interviews, questionnaires, observations, and literacy tests. The results of the study indicate that the CIRC learning model assisted by Google Sites that was developed has met the criteria of being valid, practical, and effective. The effectiveness of the model is shown by a significant increase in student learning outcomes in literacy skills. Thus, this model is worthy of being applied as an alternative literacy-based learning in the digital era.